Revenue-Raising Tax Proposals in the President's Fiscal Year 2000 Budget. (U.S. Congressional Research., 2007)
Reviews revenue-raising tax proposals in the Administration's FY2000 budget. Explains basic mechanics of the various types of tax provisions and how they are to be altered by the Administration's plan.